Efficacy of Pulsed Electromagnetic Field in Treatment of Primary Dysmenorrhea. - El-Fatah, Eman A.; Shaheen, Mohamed.M. (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
To investigate the effect of pulsed electromagnetic field (PEMF) in treatment of primary dysmenorrhea.